Characteristics of chosen lower limb anthropometric parameters in non-weight bearing and in weight-bearing conditions in school children - Leszczak, Justyna; Drzał-Grabiec, Justyna; Rykała, Justyna; Podgórska-Bednarz, Justyna; Rachwał, Maciej (European Journal of Clinical and Experimental Medicine, 2014)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. The foot is a complex biokinematic structure. In the process of phylogenesis it undergoes a number of changes that adapt it to the task of carrying heavy and dynamic loads. The development of the foot to its length is greater than to its width. The correctly developed foot is springy owing to the properly developed foot arches – the longitudinal and the transverse arches. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim of the study. The assessment of foot arches of the left and the right foot in weight- bearing and in non-weight bearing conditions in children 10-12 years of age. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study population consisted of 159 students of a primary school in Rzeszów, Poland. There were 77 boys (48%) and 82 girls (52%) in the study population. The subjects’ age was between 10 and 12 years, with 10-year-olds (51 subjects) and 11-year-olds (51 subjects) consisting 32% of the group each, and 12-year-olds (57 subjects) consisting 36% of the group. We used CQ Elektronik System for computer assessment of the feet. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. For all three measurements, Wejsflog’s index values, for both the right and the left foot, were within the range of 2.55-3.00, which means that the feet had correct arches. We observed the lowest value (2.6 - still within the norm, though) for the right foot in the third measurement – singleleg standing in weight-bearing conditions. We observed the greatest value (3.0) in the left foot in bilateral standing, with weight evenly distributed. The Clarke’s angle in non-weight bearing conditions (sitting) revealed excessive longitudinal foot arches in children, both in the right (53.5) and the left (53.4) foot. In bilateral standing, both the right foot and the left foot had proper longitudinal arches (45.2 and 42.7, respectively). In the third measurement – single-leg standing, weight bearing conditions – both the right and the left foot’s longitudinal arches were lowered (37.2 and 35.2, respectively). <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. The feet of the study population were weak – when sitting (non-weight bearing conditions), they had excessive foot arches, while in single-leg weight-bearing conditions (standing) they had lowered foot arches. This condition points at a muscle or ligament dysfunction of the feet.